Exploring the past and future: An analysis of affordable quality education in Pakistan - Hassan Sain Zohaib; Eliza Meri (BIO Web of Conferences)
The research focuses on assessing the impact of government policies, resource allocation, and teacher training on Pakistan's secondary education quality. The study aims to examine the strategies employed by the government to enhance secondary education, pinpoint the prevailing challenges, and evaluate their alignment with Sustainable Development Goal 4 (SDG-4, “Ensure inclusive and equitable quality education and promote lifelong learning opportunities for all”). A survey was conducted with respondents comprising 300 teachers and administrators from 100 public secondary schools. This data was supplemented by 15 in-depth interviews with policymakers and educational experts. The quantitative analysis indicates a strong positive correlation between government policies and student outcomes, with a correlation coefficient of 0.60. Moreover, teacher training was found to significantly impact education quality, with a correlation coefficient of 0.70. The qualitative analysis uncovered critical barriers in policy implementation and unequal resource distribution, particularly in rural areas. It is important to note that these findings are based on respondents' perceptions and do not confirm direct causal relationships between the variables. The study concludes that while Pakistan has made progress in educational reform, there is a pressing need for improved implementation, fair resource distribution, and enhanced teacher training to achieve SDG-4 and ensure affordable, high-quality secondary education. These insights offer a perception-based understanding of challenges and priorities that can inform future policy discussions and empirical investigations.